(untitled) (Vietnam Journal of Community Medicine, 2020)
Objective: To investigate the use of drugs in prescribing for treatment of hypertension in patients with stage IV chronic renal failure at An Sinh General Hospital. Objects and methods: study of retrospective,cross-sectional description of 153 medical records of patients diagnosed with hypertension with stage IV chronic renal failure who were treated in the Department of Endocrinology - Dialysis of An Sinh General Hospital, Ho Chi Minh City, from June 1 st , 2019 to May 31 st , 2020. Results: ACE inhibitors and calcium inhibitors were the two most commonly used groups of drugs. The adrenergic blocker group and the diuretic group were used less common, the Angiotensin receptor inhibitors (ARI) used the least. 75.82% of patients must use the combination regimen; in which the combination regimen of 2 drugs and 3 drugs was used the most. The most common combination pair seen in the sample in a two-drug combination regimen were ACE inhibitors and diuretics, followed by ACE inhibitors and calcium inhibitors. With a combination of 3 drug groups, the most common combination was ACE inhibitors, calcium inhibitors and adrenergic inhibitors. Conclusion: ACE inhibitors and calcium channel blockers were mainly used. Combination regimen of 2 and 3 drugs accounted for a high proportion, in which the combination of ACE inhibitors with diuretics and ACE inhibitors with calcium channel blockers and adrenergic inhibitors were mainly used.